2014
DOI: 10.1371/journal.pone.0114308
|View full text |Cite|
|
Sign up to set email alerts
|

Intrinsically Disordered and Pliable Starmaker-Like Protein from Medaka (Oryzias latipes) Controls the Formation of Calcium Carbonate Crystals

Abstract: Fish otoliths, biominerals composed of calcium carbonate with a small amount of organic matrix, are involved in the functioning of the inner ear. Starmaker (Stm) from zebrafish (Danio rerio) was the first protein found to be capable of controlling the formation of otoliths. Recently, a gene was identified encoding the Starmaker-like (Stm-l) protein from medaka (Oryzias latipes), a putative homologue of Stm and human dentine sialophosphoprotein. Although there is no sequence similarity between Stm-l and Stm, St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 126 publications
(195 reference statements)
5
56
0
Order By: Relevance
“…Surprisingly, we could found no evidence for the occurrence of the known OMP starmaker, as described for zebrafish, its orthologous protein OMM‐64 in Salmo salar and of the starmaker‐like protein in medaka (Söllner et al, ; Tohse et al, ; Bajoghli et al, ; Różycka et al, ). Starmaker and its orthologs show similarities to human‐dentin and are members of the secretory calcium‐binding phosphoprotein family (Söllner et al, ).…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Surprisingly, we could found no evidence for the occurrence of the known OMP starmaker, as described for zebrafish, its orthologous protein OMM‐64 in Salmo salar and of the starmaker‐like protein in medaka (Söllner et al, ; Tohse et al, ; Bajoghli et al, ; Różycka et al, ). Starmaker and its orthologs show similarities to human‐dentin and are members of the secretory calcium‐binding phosphoprotein family (Söllner et al, ).…”
Section: Resultsmentioning
confidence: 74%
“…Starmaker and its orthologs show similarities to human‐dentin and are members of the secretory calcium‐binding phosphoprotein family (Söllner et al, ). However, calcium‐binding phosphoproteins are poorly conserved and therefore their identification and characterization is difficult (Kawasaki and Weiss, ; Różycka et al, ). Thus in a screening of the sequenced genome of the Nile tilapia ( Oreochromis niloticus ), we also found no hints for the occurrence of a starmaker ortholog in the Oreochromis genus.…”
Section: Resultsmentioning
confidence: 99%
“…5c). Although this is not a typical response, other IDPs have been reported that show essentially no change in their far-UV spectra with increasing TMAO, including myelin basic protein (MyBP) [94] and starmaker-like protein (Stm-1) involved in biomineralization of otoliths [95]. Like PGR, each of these proteins is highly charged (28-47% of the residues are charged), although MyBP and Stm-1 have only 3-6% proline content compared to 29% for PGR.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of StmN and StmC on calcium carbonate crystallization was investigated using a slow diffusion method previously used for full-length Stm (18,35). Crystallization solution (300 ml) consisted of 0.155 or 1.55 mM concentration of protein fragments in TNaG buffer and 10 mM CaCl 2 .…”
Section: In Vitro Calcium Carbonate Mineralization Assaymentioning
confidence: 99%